Optimization Constrained of the Lifetime of the CBN 7050 during the Machining of Steel 100Cr6 - Slimane Benchiheub (Japanese Society of Tribologists, 2009)
The purpose of the study is to evaluate the cutting performances of tool material CBN 7050 produced during turning bearing steel 100Cr6 soaked. Tests of tools' wear of long life were carried out. The method adopted for the realization of these tests is that of the experimental designs. A mathematical models validated by the criterion of Fisher, allow to predict the lifetime T of the tested tool material, and the expected roughness Ra (surface integrity). They are necessary for optimization and the industrial exploitation. The roughness Ra was taken as the same moment as the wear Vb. The experimental results have a better output in terms of lifetime (T = 62.94 min.), and surfaces roughness (Ra = 0.25 to 1.01 μm) to Vc = 120 m/min. (cutting speed) include in borders for those of the grinding. Non linear optimization of the lifetime material (CBN 7050) under the surface state (Ra) taken as inequality constraint to Matlab mean allows to release an optimum (T = 61.73 min.) to Vcopt = 120 m/min. near to the experimental value with 98%.